Arbuscular Mycorrhiza Improves Photosynthesis and Restores Alteration in Sugar Metabolism in Triticum aestivum L. Grown in Arsenic Contaminated Soil - Gupta, Samta; Thokchom, Sarda Devi; Kapoor, Rupam (Frontiers in Plant Science, 2021)
Contamination of agricultural soil by arsenic (As) is a serious menace to environmental safety and global food security. Symbiotic plant-microbe interaction, such as arbuscular mycorrhiza (AM) is a promising approach to minimize hazards of As contamination in agricultural soil. Even though potential of AM fungi (AMF) in redeeming As tolerance and improving growth is well recognized, the detailed metabolic and physiological mechanisms behind such beneficial effects are far from being completely unraveled. The present study investigated the ability of an AM fungus, Rhizophagus intraradices, in mitigating As mediated negative effects on photosynthesis and sugar metabolism in wheat (Triticum aestivum) subjected to three levels of As viz. 0, 25, and 50 mg As kg-1 soil, supplied as sodium arsenate. As exposure caused significant decrease in photosynthetic pigments, Hill reaction activity, and gas exchange parameters such as net photosynthetic rate, stomatal conduction, transpiration rate, and intercellular CO2 concentration. In addition, As exposure also altered the activities of starch hydrolyzing, sucrose synthesizing and degrading enzymes in leaves. Colonization by R. intraradices not only promoted plant growth, but also restored As mediated impairments in plant physiology. The symbiosis augmented the concentration of photosynthetic pigments, enhanced Hill reaction activity, and improved leaf gas exchange parameters and water use efficiency of T. aestivum even at high dose of 50 mg As kg-1 soil. Furthermore, inoculation with R. intraradices also restored As mediated alteration in sugar metabolism by modulating the activities of starch phosphorylase, α-amylase, β-amylase, acid invertase, sucrose synthase, and sucrose phosphate synthase in leaves. This ensured improved sugar and starch levels in mycorrhizal plants. Overall, the study advocates the potential of R. intraradices in bio-amelioration of As induced physiological disturbances in wheat plant.